Passive Heymann nephritis in pre- and post-natal rats. - Challice, J. (1986)
Passive Heymann nephritis (PHN) was induced in pre- and post-natal rats by a single intra-peritoneal injection of 0.2 ml of a rabbit anti-rat kidney fraction 3 (rKF3) antibody. Immune complex formation occurred only in those glomeruli or parts of glomeruli which were open to the circulation. Double staining of kidney sections for the glomerular nephritogenic antigen and rabbit IgG, 2 days after the injection of the antibody showed an identical distribution of both components in the glomeruli. In rats killed more than 4 days after the injection of the anti-rKF3 antibody, the nephritogenic antigen could be demonstrated in the subcapsular glomeruli, in the absence of rabbit IgG; and the same applied when the kidneys had reached maturity. When the injected antibody was expected to be present in the circulation, no nephritogenic antigen was demonstrated in the glomeruli in the absence of the heterologous IgG. These observations indicate that the nephritogenic antigen appears in the glomerulus at the same time as the glomerular capillary loops open to the circulation. Unlike PHN in the adult rat, the immune complexes in the glomeruli of neonatal rats do not persist longer than 84 days.